Between ecological convictions and practical considerations – profiles and motivations of residents in car-free housing developments in Germany and Switzerland. - Baehler, Daniel; Rérat, Patrick (Copernicus Publications, 2020)
Automobility still dominates transport and space in most European cities. However, more and more initiatives are being taken to encourage a transition towards low-carbon mobility. One of these is car-free housing, where residents commit to living without a private car. This paper addresses their profiles and motivations based on a questionnaire survey (N=571) and interviews (N=50) in nine housing developments in Germany and Switzerland. Residents are characterised by an overrepresentation of families and people with a high level of education, two population groups that are usually more motorised than average. Their motivations and long-term commitment to living car-free can be explained by not only practical reasons (e.g. availability of alternative modes) but also ecological awareness and social values (as shown by the importance of cooperative housing). This paper sheds light on these urban laboratories where the principles of a post-car system are implemented.
Keywords: Autofreie Siedlung; Autofreies Wohnen; Autofreiheit; Mobilität